EXAMINING SPEECH ACTS AS LINGUISTIC SIGNS OF COERCION IN MALAYSIAN PARLIAMENTARY DISCOURSE ON LANGUAGE POLICY - Nazira Osman, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
In a political discourse like a parliamentary debate, speech acts are used to convince or persuade others to believe in parliamentarians’ course of actions. The speech acts are used as part of coercive strategies when the third level, i.e., the perlocutionary acts, are manipulated for the purpose of getting an immediate effect through a speaker’s words. The acts include persuading, convincing, scaring, insulting, and getting the addressee to do something. This study examined the Malaysian Parliamentarians’ (MPs) discursive statements on a debatable language issue; the use of English in the teaching and learning of Science and Mathematics. Debate transcripts (hansards) that consist of speeches of the government-alliance MPs were analysed to see how the speech acts were adopted as coercive strategies in positioning themselves and the policy at the parliamentary level. Adopting a semiotic approach, this research investigates the use of linguistic features of coercion in a large pool of data collected from verbatim written transcripts of the Dewan Rakyat, which were available online. The results of the study indicated that a high number of coercive signs were adopted by the MPs when deliberating support for the policy implementation. Moreover, inferences made on the manipulations of the coercive signs illustrated that the MPs would opt for the signs that helped show their credibility and accountability in relation to the policy implementation. This study is significant in revealing the Malaysian parliamentarians’ political stances in dealing with a debatable language policy by using speech acts as coercive linguistic signs.